Synchronizing between Lasswell’s Communication Model and Abram’s Critical Orientation as a Sophisticated Concept of Literary Communication and Its Associated Studies - Sarif Syamsu Rizal (Universitas Dian Nuswantoro, 2019)
Abstract. This scientific article is entitled